1976
DOI: 10.2135/cropsci1976.0011183x001600030010x
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Carbohydrate in the Spring Herbage of Temperate Grasses1

Abstract: Nonstructural carbohydrates are sources of readily available energy that enhance rumen microbial activity and forage utilization. Experiments were conducted in Pennsylvania and West Virginia to determine the effect of maturity on total nonstructural carbohydrate (TNC) concentrations in spring herbage of eight grass species and determine TNC concentrations in herbage at immature and mature growth stages on a given day. The grasses were fertilized early each spring and summer with 0, 60, 120, or 240 kg N/ha.Dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Thus, August‐harvested leaves were chronologically older, perhaps explaining the reduction in the TNC. Jung et al (1976) noted that the TNC concentrations were reduced as plants matured physiologically but an effect of increasing chronological age was not found.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, August‐harvested leaves were chronologically older, perhaps explaining the reduction in the TNC. Jung et al (1976) noted that the TNC concentrations were reduced as plants matured physiologically but an effect of increasing chronological age was not found.…”
Section: Resultsmentioning
confidence: 97%
“…Grasses, even at the morning sampling, contained more than the 80 g kg −1 TNC required for proper fermentation of grass silage (Jung et al, 1976) The TNC influence the amount and ratio of volatile fatty acids produced in the rumen (Bowden et al, 1968), which affects the efficiency of forage utilization. Reid et al (1966) observed that the palatability of grasses increased with increasing WSC concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest mean TNC concentration was 43 g kg )1 ADW, occurring on 13 September and the highest mean TNC concentration was 335 g kg )1 ADW occurring on 17 May. The TNC concentrations were generally above 80 g kg )1 DM required for proper fermentation of grass silage (Jung et al, 1976) although higher values should benefit fermentation and nutrient retention in silage.…”
Section: Total Non-structural Carbohydrates Concentrationsmentioning
confidence: 90%
“…The TNC concentrations were generally above 80 g kg )1 DM required for proper fermentation of grass silage (Jung et al, 1976) although higher values should benefit fermentation and nutrient retention in silage.…”
Section: Total Non-structural Carbohydrates Concentrationsmentioning
confidence: 96%
“…The perception that alternative pasture grasses are of poorer nutritive value than perennial ryegrass is largely the result of studies in which management was based on perennial ryegrass (to the detriment of the alternative species) or involved defoliation of different species at exactly the same time (Greenhalgh and Reid, 1969; Jung et al. , 1976; Balasko et al.…”
Section: Introductionmentioning
confidence: 99%